Dermoscopic Features of Psoriatic Nails and Their Correlation to Disease Severity - Zeinab R. Mashal; Emad Eldin A. Elgamal; Mohamed S. Zaky; Mohamed L. Elsaie (Dermatology Research and Practice)
Background. Nail psoriasis is a challenging chronic condition affecting patients functionally and psychologically. Nail involvement is observed in 15–80% of psoriatic patients with occasional presence of isolated nail psoriasis. Objectives. To evaluate dermoscopic features of nail psoriasis and correlate them clinically. Methods. The study included fifty subjects with nail psoriasis. Psoriasis skin and nail severity was evaluated using psoriasis area severity index (PASI) and nail psoriasis severity index (NAPSI). Dermoscopy of the nails (onychoscopy) was performed, and features were recorded and analyzed. Results. The most common clinical and dermoscopic findings were pitting (86%) and onycholysis (82%). Among all dermoscopic features of nail psoriasis, only longitudinal striations and subungual hyperkeratosis were significantly higher in patients with moderate to severe psoriasis than in patients with mild psoriasis (P=0.028; P=0.042, respectively). PASI scores correlated positively but none significantly with NAPSI scores (r = 0.132, P=0.360), and similarly, no significant correlation was observed between the duration of psoriasis and the dermoscopic NAPSI (r = 0.022, P=0.879). Conclusion. Dermoscopy can serve as a useful tool for early diagnosis of psoriatic nail changes not always visible to the naked eye and is a non-invasive easy-to-use confirmatory tool for nail changes in psoriatic disease or in isolated nail involvement.